The Agony of Liberation Theology - Luiz Carlos Susin (Religions, 2025)
The aim of this article is to understand why Liberation Theology remains in dispute, placed between life and death, in the condition of agony as its own place. To this purpose, it analyzes the malaise and misunderstandings that accompany it, especially contemporary ones. It seeks to situate Liberation Theology in its connection with history and today’s society in its conflicts and sufferings. This way, it seriously considers theological places as social and historical places and vice versa. It then deepens its epistemological vocation with the principle of liberation together with the principle of mercy and the principle of hope. It concludes with the internal approaches of this theology as Theologies for the Kingdom of God, affirmative theologies, and Theology of the God of the Kingdom, theology of kenosis, of God on the crosses of those who suffer.